Neuroergonomics on the Go: An Evaluation of the Potential of Mobile EEG for Workplace Assessment and Design. (February 2023) - Wascher, Edmund; Reiser, Julian; Rinkenauer, Gerhard; Larrá, Mauro; Dreger, Felix A.; Schneider, Daniel; Karthaus, Melanie; Getzmann, Stephan; Gutberlet, Marie; Arnau, Stefan
Objective: We demonstrate and discuss the use of mobile electroencephalogram (EEG) for neuroergonomics. Both technical state of the art as well as measures and cognitive concepts are systematically addressed. Background: Modern work is increasingly characterized by information processing. Therefore, the examination of mental states, mental load, or cognitive processing during work is becoming increasingly important for ergonomics. Results: Mobile EEG allows to measure mental states and processes under real live conditions. It can be used for various research questions in cognitive neuroergonomics. Besides measures in the frequency domain that have a long tradition in the investigation of mental fatigue, task load, and task engagement, new approaches—like blink-evoked potentials—render event-related analyses of the EEG possible also during unrestricted behavior. Conclusion: Mobile EEG has become a valuable tool for evaluating mental states and mental processes on a highly objective level during work. The main advantage of this technique is that working environments don't have to be changed while systematically measuring brain functions at work. Moreover, the workflow is unaffected by such neuroergonomic approaches.